Analysis the Influence of Service Quality, Social Media, Price Strategy to Purchasing Decisions and Store Loyalty - Yanti Mayasari Ginting; Fransiska Natalia Ralahallo; Obet Eko Wiranto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of service quality, social media, price strategy on purchasing decisions and store loyalty. The data used in this study is primary data obtained from the distribution of questionnaires. The population in this study are customers who have purchased products at PT Bintang Lima Pekanbaru. The sample in this study used non-probability sampling by using purposive sampling method. Respondents who answered the list of statements were people aged 17 years and over in the city of Pekanbaru. The number of samples in this study amounted to 150 samples. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the variables of service quality, social media, price strategy have a significant effect on purchase decision, while the service quality and social media have no significant effect on store loyalty, but the price strategy and purchase decision have a significant effect on store loyalty.